Concept of controlling the proceedings in the notary - Колпаков, Валерій Костянтинович; Довженко, Інна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article is based the content of notaries control production and the concept of this production is formulated. Is proven the expediency of two comprising notaries control - control of the organization of notary and the control of the accomplishment of notary’s actions. In connection with this are isolated two corresponding forms of control productions in the sphere indicated